Artifical Intelliegnce (AI) Ethics Meets Ubuntu: Towards A Context-Aware Governance Model For Sustainable Innovation In Africa (International Journal of Scientific Research and Management (IJSRM), 2025)
Artificial intelligence (AI) is rapidly diffusing across African societies, yet most governing frameworks arrive as de-contextualised imports that privilege individual autonomy and post-hoc liability. Drawing on Ubuntu, an indigenous relational philosophy that defines personhood through reciprocal obligation, this paper conducts a systematic review (2018 April 2025) of peer-reviewed and grey scholarship on Ubuntu-centred AI ethics. Thirty three eligible studies are interrogated through a pluralistic lens that couples Ubuntu ethics with relational autonomy theory and socio-technical systems analysis. Nine recurrent themes are identified, including communal data stewardship, collective responsibility, and contextual conceptions of fairness, ecological sustainability and intersectionality. While Ubuntu offers a powerful counter-narrative to data colonialism and responsibility gaps, empirical evidence of its operationalisation remains sparse and uneven. To translate ethos into practice, the article proposes a five-layer governance architecture including (1) Community Data Trusts, (2) Relational Design Praxis, (3) Harm Reconciliation Panels with risk-bond funding, (4) Ecological Stewardship Protocols, and (5) Developer Benefit Realisation. This modular model embeds Ubuntu values across the AI life-cycle while remaining compatible with statutory regimes and technical constraints. The study concludes that Ubuntu-aligned governance can enhance trust, equity and sustainability in African AI deployments, but realisation depends on sustained capacity-building, intersectional safeguards and iterative empirical evaluation.